A repetição da construção da interioridade do sujeito em ambulatórios didáticos: uma etnografia por meio da circulação entre hábitos, adicções, dependências e prazeres com drogas e/ou substâncias - Chaves Júnior, Wander Wilson (2019)
This research sets off from an ethnographic experiment made in two university ambulatories dedicated to drug dependence treatment in São Paulo. These ethnographies situate drugs between open and closed flux of public mental health treatment. In this, the research is no longer positioned in front of old asylum psychiatry as, today, people walk in and out of institutional buildings. Not only people, but corpses, liquid, bacteria, litter, concepts, molecules, subjectivities… Much comes in, and much comes out and these paths led to the reflection on the effects of current policies over drugs and addiction in the passing from a disciplinary society as announced by Michel Foucault, to a contemporary control society, as sketched by Gilles Deleuze. So-called drugs have been prohibited for a over a century. Nonetheless, what we understand as dependency emerged in the camp of discourses already in the 18th Century. Fieldwork was led through the articulation of diverse concepts: habits, addictions and dependencies. Likewise, these concepts, as well as the multiple realities which the fieldwork accesses, emerge in heterogeneous manner, as with drugs themselves, which emerge either as chemical substances, or as medications, or even in a mixed manner. Openness and closedness, decentralization and verticalization are two pair of practices that appear consistently throughout the analysis. Control society does not abdicate from its closures and verticalizations, even if, when operating in open spaces and continuous flux, diverse unities are recombined. The focus of this work is the analysis of the practices that produce an exchange of concepts, realities and articulations that manage to disjoint, merge and emerge at the same time. Verticalization is always present in the cutting and refoundation of this central unity, be it in the ambulatory itself, or in the individual subject with their life stories. The discourses produced over drug addiction also touch upon interiorization, many times upon an escape from oneself. This relation is constantly compared to marriage, picturing the image of an extreme situation within the process of interiorization of the individual. The research started with walks towards the field – in the terrain of geography – then inhabiting history, cutting through the present which invokes history. From this starting point, the research exposes itself in a continuous flow of writing, without a theme-based grouping of chapters, which leads to the research’s stipulation of small cuts of flux